TOWARD HYBRID TEAMS: A PLATFORM TO UNDERSTAND HUMAN-COMPUTER COLLABORATION DURING THE DESIGN OF COMPLEX ENGINEERED SYSTEMS. (May 2020) - Song, B.; Soria Zurita, N. F.; Zhang, G.; Stump, G.; Balon, C.; Miller, S. W.; Yukish, M.; Cagan, J.; McComb, C.
Abstract: Human-computer hybrid teams can meet challenges in designing complex engineered systems. However, the understanding of interaction in the hybrid teams is lacking. We review the literature and identify four key attributes to construct design research platforms that support multi-phase design, hybrid teams, multiple design scenarios, and data logging. Then, we introduce a platform for unmanned aerial vehicle (UAV) design embodying these attributes. With the platform, experiments can be conducted to study how designers and intelligent computational agents interact, support, and impact each other.